Green Economy Transition in Vietnam: Assessing Unemployment and Life Expectancy Dynamics - Salvador, Jude Anne P.; Santiago, Elisha Angel Anne G.; Cabauatan, Ronaldo R.; Rosete , Marie Antoinette L. (Indonesian Journal of Social and Environmental Issues (IJSEI), 2024)
The study assesses how the environmental factor influences the social dimension of the global green economy index. Covering the period from 1991 to 2023, the study utilizes a descriptive-quantitative approach with time-series data. It employs the Ordinary Least Squares (OLS) model in EViews to examine the connections between these variables and socioeconomic results. The findings reveal that CO2 emissions negatively affect life expectancy, while forest area contributes positively. Nevertheless, the use of renewable energy does not demonstrate a statistically significant impact on life expectancy. Similarly, none of the independent variables—CO2 emissions, forest area, and renewable energy consumption—were statistically significant for unemployment. The autoregressive term (AR(1)) is highly significant, indicating that past unemployment rates strongly influence current unemployment levels. These results emphasize the importance of addressing environmental factors to improve life expectancy, while also highlighting the limited direct impact of green economy variables on unemployment in Vietnam.